2015
DOI: 10.1155/2015/476508
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Chromosomal Aberrations and Their Clinical Significance in Renal Neoplasms

Abstract: The most common form of malignant renal neoplasms is renal cell carcinoma (RCC), which is classified into several different subtypes based on the histomorphological features. However, overlaps in these characteristics may present difficulties in the accurate diagnosis of these subtypes, which have different clinical outcomes. Genomic and molecular studies have revealed unique genetic aberrations in each subtype. Knowledge of these genetic changes in hereditary and sporadic renal neoplasms has given an insight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 257 publications
(299 reference statements)
0
23
1
Order By: Relevance
“…Elevated mRNA expression was the most alteration. Tumorigenesis and the progression of RCC are complex and multi-faceted, and genetic alteration plays an important role in this process (35). We found a low to high correlation among the differentially expressed CXC chemokines, suggesting that these cytokines play a synergistic role in the tumorigenesis and progression of RCC.…”
Section: Discussionmentioning
confidence: 66%
“…Elevated mRNA expression was the most alteration. Tumorigenesis and the progression of RCC are complex and multi-faceted, and genetic alteration plays an important role in this process (35). We found a low to high correlation among the differentially expressed CXC chemokines, suggesting that these cytokines play a synergistic role in the tumorigenesis and progression of RCC.…”
Section: Discussionmentioning
confidence: 66%
“…The loss of one copy of chromosomes 1, 2, 6, 10, 13, 17, 21 and Y occurs in the majority of chRCC cases. Since losses of chromosomes 1 and Y have been reported in benign oncocytoma [5,16,18,19], we speculated that only loss of chromosomes 2, 6, 10, 13, 17 and 21 may be associated with outcome in chRCC patients. The frequencies of loss of these chromosomes were similar in both the TCGA-KICH and the Swiss cohort.…”
Section: Chromosomal Loss and Patient Outcomementioning
confidence: 99%
“…Chromophobe renal cell carcinoma (chRCC) is the third most common histological subtype of RCC and accounts for approximately 5-7% of RCC [1][2][3]. Although chRCC patients have better prognoses than patients with clear cell RCC (ccRCC) or papillary RCC (pRCC) [1][2][3][4][5], about 5-7% of patients die of metastatic disease [4,6,7]. Therefore, it is of utmost importance to identify prognostic factors, which can better predict the small patient group with clinical progression after surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that genetic factors may have a critical influence on the aetiology of RCC. Several studies have confirmed the role of genetic factors in the development of RCC [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 95%